2022
DOI: 10.1002/kjm2.12576
|View full text |Cite
|
Sign up to set email alerts
|

Individualized positive end‐expiratory pressure with and without recruitment maneuvers in obese patients during bariatric surgery

Abstract: This study aimed to determine whether regular recruitment maneuvers (RMs) are essential for obese patients (OPs) undergoing elective laparoscopic bariatric surgery (LBS) during intraoperative ventilation with individualized positive end‐expiratory pressure (PEEP). Patients were randomly assigned to two arms: the RM + PEEP−EIT arm consisted of individualized PEEP titrated by electrical impedance tomography (EIT) with two regular RMs and the PEEP−EIT arm consisted of individualized PEEP titrated by EIT without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The improved lung compliance at T1, T2, and T4 implies fewer PPCs. Furthermore, the PaO 2 /FiO 2 did not improve significantly in the experimental group but was significantly higher at T3 while the total complication rate was significantly reduced, which is consistent with previous reports [ 5 , 13 , 33 ]. The optimizing ventilation strategies during OLV were closely associated with fewer PPCs and better perioperative oxygenation [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The improved lung compliance at T1, T2, and T4 implies fewer PPCs. Furthermore, the PaO 2 /FiO 2 did not improve significantly in the experimental group but was significantly higher at T3 while the total complication rate was significantly reduced, which is consistent with previous reports [ 5 , 13 , 33 ]. The optimizing ventilation strategies during OLV were closely associated with fewer PPCs and better perioperative oxygenation [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Customized PEEP enhances oxygen levels, end-tidal lung volume (EELV), and respiratory function when ventilating patients during surgery. Nevertheless, these benefits may diminish shortly after removing the endotracheal tube [ 11 13 ]. Using driving pressure-guided ventilation during OLV decreases PPCs compared to traditional lung protective ventilation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the EIT-guided PEEP level was found to be lower compared with the lower PEEP/F I O 2 table [12 ▪ ]. The same approach was used in a study on obese patients during bariatric surgery with the PEEP set either with or without a preceding recruitment maneuver, showing higher intraoperative C rs in the recruitment group but no differences in the postoperative outcomes [13].…”
Section: How Can Electrical Impedance Tomography Help In Setting Posi...mentioning
confidence: 99%
“…In that study, the EIT-guided PEEP level was found to be lower compared with the lower PEEP/F I O 2 table [12 & ]. The same approach was used in a study on obese patients during bariatric surgery with the PEEP set either with or without a preceding recruitment maneuver, showing higher intraoperative C rs in the recruitment group but no differences in the postoperative outcomes [13]. Detection of regional respiratory system compliance and its changes as a tool for setting positive end-expiratory pressure When airway pressure is measured in parallel with the EIT examination, regional C rs can be determined from EIT data by dividing the TIV values with the driving pressure.…”
Section: Detection Of Spatial Distribution Of Ventilation and Its Use...mentioning
confidence: 99%